Steel slag and phosphate nutrition of corn inoculated with arbuscular mycorrhizal fungi - Nunes, Anita Bueno de Camargo; Saggin Júnior, Orivaldo José; Silva, Eliane Maria Ribeiro da; Pinto, Flávio Araújo; Santos, Jessé Valentim dos; Carneiro, Marco Aurélio Carbone (Pesquisa agropecuaria brasileira, 2019)
The objective of this work was to evaluate the effect of the use of steel slag as a soil acidity corrective and of mycorrhizal fungi associated with phosphate fertilization on corn plants. The study was performed in a greenhouse, using 3-kg pots with a Typic Haplorthox, in a 4x5x2 factorial arrangement, with four acidity correction treatments (C1, correction with dolomitic limestone at a dose of 4 Mg ha-1; C2, correction with steel slag at a dose of 4 Mg ha-1; C3, correction with a 1:1 mixture of 2 Mg ha-1 dolomitic limestone and 2 Mg ha-1 steel slag; and C4, control, without pH correction), five phosphorus doses (0, 42, 95, 213, and 480 mg dm-3), and the presence or absence of two arbuscular mycorrhizal fungi (Rhizophagus clarus and Gigaspora margarita), with five replicates. Steel slag was efficient in correcting soil pH and providing Ca and Mg for the plants; therefore, it could replace limestone. The inoculation with R. clarus and G. margarita, associated with P doses of 42, 95, and 213 mg dm-3, improved the development of corn plants after 45 days, resulting in greater plant height, stem diameter, leaf area, and shoot and root dry matter. Resumo: O objetivo deste trabalho foi avaliar o efeito do uso de escória de siderurgia como corretivo da acidez do solo e de fungos micorrízicos associados à adubação fosfatada em plantas de milho. O trabalho foi conduzido em casa de vegetação, tendo-se utilizado vasos com 3 kg de Latossolo Vermelho distrófico, em arranjo fatorial 4x5x2, com quatro tratamentos corretivos da acidez (C1, correção com calcário dolomítico na dosagem de 4 Mg ha-1; C2, correção com escória de siderurgia de aciaria na dosagem de 4 Mg ha-1; C3, correção com a mistura 1:1 de 2 Mg ha-1 de calcário dolomítico e 2 Mg ha-1 de escória; e C4, controle, sem correção de pH), cinco doses de fósforo (0, 42, 95, 213 e 480 mg dm-3), e presença ou ausência de dois fungos micorrízicos arbusculares (Rhizophagus clarus e Gigaspora margarita), com cinco repetições. A escória foi eficiente em corrigir o pH do solo e fornecer Ca e Mg para as plantas; portanto, pode substituir o calcário. A inoculação com R. clarus e G. margarita, associada às doses de 42, 95 e 213 mg dm-3 de P, promoveu melhoras no desenvolvimento de plantas de milho após 45 dias, tendo resultado em maiores altura, diâmetro do colo, área foliar e matéria seca das raízes e da parte aérea das plantas.